Alternative paths of diversification for developing countries. Issue 4 (22nd July 2022) - Eum, Wonsub; Lee, Jeong‐Dong
Abstract: This study analyzes different diversification options of countries at different economic stages, and complements the previous diversification literature from the perspective of coevolution between production and technological capability. This study points out that path dependence theories concerning diversification patterns of countries cannot give useful policy implications to developing countries, because they can only take either the "high‐risk high‐return" or "low‐risk low‐return" tracks. The analysis includes 84 countries from 1980 to 2005, and studies the close relationship between product space and knowledge space to understand the alternative drivers of product and technological diversification. The results show that countries at different income levels have different factors of diversification. Specifically, production capability of developing countries guides future technological diversification, and technological capability of developed countries leads to product diversification in related products.